Consumer Protection on pertamina Fuel Quality in the Pertamax-Pertalite Adulteration case: Wahbah Az-Zuhaili's Perspective - Cicih Aninda; Fauziah Lubis (Yayasan Lembaga Studi Makwa, 2025)
This study examines consumer protection concerning the quality of Pertamina’s fuel in the case of Pertamax adulterated with Pertalite, analyzed through the perspective of Wahbah Az-Zuhaili. The background of this research stems from the increasing allegations of fuel adulteration by individuals within PT Pertamina Patra Niaga and its subsidiaries, which have caused significant losses to both society and the state. The study aims to analyze the forms of consumer protection law violations in this case and to review the legal solutions from both positive law and Islamic law perspectives. This research employs a normative legal method with a qualitative approach, utilizing primary legal materials such as Law No. 8 of 1999 on Consumer Protection, alongside secondary materials including legal literature and academic journals. The findings indicate that the practice of mixing Pertamax and Pertalite violates Articles 7 and 8 of the Consumer Protection Law (UUPK) as it involves trading goods inconsistent with their labeling and quality standards. From the Islamic perspective, such an act constitutes tadlīs fī al-jawdah (deception in product quality), which is strictly prohibited, as emphasized by Wahbah Az-Zuhaili in al-Fiqh al-Islāmī wa Adillatuhu. The state holds both legal and moral responsibilities as waliy al-amr to uphold justice through effective supervision (hisbah) and firm law enforcement. In conclusion, the practice of fuel adulteration represents a violation of both national and Sharia law. Therefore, reform in energy distribution governance, transparency in monitoring, and consumer education are essential to prevent similar fraudulent acts in the future